Teologi Inkarnasi Sebagai Landasan Praksis Pembentukan Perilaku Sosial Masyarakat - Hironimus Resi; Teresia Noiman Derung (KENOSIS: Jurnal Kajian Teologi, 2022)
The theology of the incarnation is the embodiment of God's highest love for man as the redeemer of man. The event of the incarnation became a very real sign of God's love in all human life that was in line with Him "Imago Dei". However, in the development of science and technology, the love of God manifested in the image of man who is similar to God is disrupted into a tool used for personal satisfaction that results in violence both physically and mentally. The purpose of the study, describes the meaning of the incarnation in relation to the praxis of the formation of social behavior of society. The method used is descriptive qualitative with a contextual approach. Results of the study; first, the theology of the incarnation is the definitive embodiment of God's love for man so that man as a social being is called to love others as the embodiment of His love. Second, in love, God forgives sinful people. The experience of God's infinite forgiveness, as a foundation for forgiving others including enemies. Third, love requires self-sacrifice to serve others who suffer because of life's problems. Followers of Christ are called out of themselves, bearing witness by serving in love. In conclusion, the Incarnation is the embodiment of God's love for the salvation of man. Love is the foundation of praxis for the formation of human behavior in people's lives. In that love, too, man is called to love, forgive and sacrifice himself for others in the image of God.AbstrakTeologi inkarnasi merupakan perwujudan kasih Allah yang tertinggi kepada manusia sebagai penebusan dosa manusia. Peristiwa inkarnasi menjadi tanda kasih Allah yang sangat nyata di dalam seluruh kehidupan manusia yang secitra dengan-Nya “Imago Dei”. Namun, dalam perkembangan ilmu pengetahuan dan teknologi, kasih Allah yang terwujud dalam gambaran manusia yang serupa dengan Allah mengalami disrupsi menjadi alat yang digunakan untuk kepuasan pribadi sehingga mengakibatkan kekerasan baik fisik maupun mental. Tujuan kajian, mendeskripsikan makna inkarnasi dalam hubungan dengan praksis pembentukan perilaku sosial masyarakat. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan kontekstual. Hasil kajian; pertama, teologi inkarnasi merupakan perwujudan kasih Allah yang definitif kepada manusia sehingga manusia sebagai makhluk sosial dipanggil untuk mengasihi sesama sebagai perwujudan kasih-Nya. Kedua, dalam kasih, Allah mengampuni manusia yang berdosa. Pengalaman akan pengampunan Allah yang tak terbatas, sebagai landasan untuk mengampuni sesama termasuk musuh. Ketiga, kasih menuntut pengorbanan diri untuk melayani sesama yang menderita karena persoalan hidup. Pengikut Kristus dipanggil keluar dari dirinya sendiri, memberi kesaksian dengan melayani dalam kasih. Kesimpulan, peristiwa inkarnasi merupakan perwujudan kasih Allah demi keselamatan manusia. Kasih itu menjadi landasan praksis pembentukan perilaku manusia dalam kehidupan masyarakat. Dalam kasih itu pula, manusia dipanggil untuk mengasihi, mengampuni dan mengorbankan diri bagi sesama sebagai citra Allah.